Knowledge and Attitude of Healthcare Providers on Managing Pre-Eclampsia and Eclampsia During Antenatal Care in Mwanza Region-Tanzania - Anna Sangito Pallangyo BSc, MSc; Saada Ali Seif BSc, MSc, PhD (SAGE Publishing, 2023)
Background Pre-eclampsia and eclampsia are the second-leading causes of maternal death. Health care providers have a critical role in preventing and managing these conditions. Lack of knowledge among healthcare providers on managing pre-eclampsia and eclampsia has been reported in other parts of Tanzania, but more information is needed in other parts of the country so as to design appropriate targeted interventions. Hence, this study assessed the knowledge and attitude of healthcare providers on the management of pre-eclampsia and eclampsia in the Mwanza region of Tanzania. Method A facility-based analytical cross-sectional study was conducted from April to May 2022 among 157 health care providers in the Mwanza region. A simple random sampling method was used to select districts and dispensaries, while a census method was used to recruit health care providers. A self-administered questionnaire was used for data collection. A descriptive statistics analysis was used to determine the distribution of background information of healthcare providers. Inferential statistics were used to determine the association between variables by using a chi-square test and logistic regression. A statistically significant variable in the final model was declared with a 95% confidence interval and a p-value of 0.05. Results The study results showed that only 40 (25%) of healthcare providers had adequate knowledge and 56.69% had positive attitude towards the management of pre-eclampsia and eclampsia. Knowledge was predicted by having more years of working experience (1-5 years) (AOR: 0.12, 95% CI 0.03-0.53, p-value 0.005) and working in a health center (AOR: 4.58, 95% CI 1.14-18.36, p-value 0.023). For attitude, no variable was significantly associated with it. Conclusion The study showed that the majority of the participants had inadequate knowledge of the management of pre-eclampsia or eclampsia, despite the positive attitude they possessed. This implies that HCP may be struggling to identify the signs and symptoms of the condition in pregnant women, and this could lead to delays in diagnosis despite believing that it is important to early diagnose the condition. To address this issue, it's crucial to invest in continuing medical education and training programs for healthcare providers to update their knowledge.